A VERBAL AND NON-VERBAL SIGNS FOUND IN DESCENDANTS MOVIE POSTER - Ni Wayan Sinta Laras Hati; I Made Yogi Marantika (CV. Shofanah Media Berkah, 2024)
The objective of this study is to determine and analyse the verbal and non-verbal signs within the movie poster of